2020
DOI: 10.21272/mmi.2020.4-01
|View full text |Cite
|
Sign up to set email alerts
|

Innovations in government management of the healthcare system: forecasting of covid-19 consequences in social, investment and business development

Abstract: This paper summarizes the arguments and counterarguments within the scientific discussion on the issue of the need for an innovative policy in the area of health protection at the link with the transformation of the social and economic development of the country through the pandemic COVID-19. The main goal of this study is to predict two scenarios for the development of the main indicators of the country's socio-economic development: considering the pandemic COVID-19 and the possible course of events without t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…On the other hand, the findings showed that the COVID-19 pandemic was accompanied by suicidal ideation due to social isolation and social restrictions, fear, unemployment, and financial factors (Hinrichs and Bundtzen, 2020;The Lancet, 2020;Vasylieva et al, 2020).…”
Section: Methodology and Research Methodsmentioning
confidence: 99%
“…On the other hand, the findings showed that the COVID-19 pandemic was accompanied by suicidal ideation due to social isolation and social restrictions, fear, unemployment, and financial factors (Hinrichs and Bundtzen, 2020;The Lancet, 2020;Vasylieva et al, 2020).…”
Section: Methodology and Research Methodsmentioning
confidence: 99%
“…Modernization of the healthcare system's infrastructure positively affects public health and stimulates economic growth due to the improvement of the quality and productivity of the workforce. Lyeonov et al (2021a); Lyeonov et al (2021b); Vasylieva et al (2020); Ziabina, Kwilinski, Belik (2021) also highlighted channels of public health care system influence on the country's economic development. Finally, GDP growth stimulates investing in the development of the green economy, and the improvement of the environment allows for the allocation of investments in fixed assets and accelerates economic growth (Tomchuk et al (2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Authors from different countries investigated the multidirectional impact of the COVID-19 pandemic on the social and economic development of territorial units. Many social issues have been raised due to the long-term effect of the uncertainty surrounding the coronavirus pandemic [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. An important topic was raised in one study [24] regarding the creation of gender-sensitive policies to counter the negative impact of the pandemic.…”
Section: Introductionmentioning
confidence: 99%